A Review of Medicinal Uses, Phytochemistry and Biological Activities of Bolusanthus speciosus (Bolus) Harms (Fabaceae) - Alfred Maroyi, (Journal of Pharmacy and Nutrition Sciences, 2020)
Bolusanthus speciosus (Bolus) Harms is a deciduous and ornamental tree with its different parts used traditionally to treat various diseases. The main aim of this review is to provide an overview and critical analysis of the medicinal uses, phytochemistry, and biological activities of B. speciosus. The information presented in this study was gathered using various databases such as PubMed, Taylor and Francis imprints, Springer, NCBI, Google scholar and Science direct, and review of books, journal articles and other scientific publications kept in the university library. The articles published between 1933 and 2020 were used in this study. The bark, leaf and stem infusion of B. speciosus are mainly used for cleansing blood and as an emetic, and a traditional medicine for abdominal pains, kidney problems, sexually transmitted infections and stomach problems. Phytochemical compounds identified from the leaves, root bark, root wood, seeds and stem bark of B. speciosus include alkaloids, essential oils, flavonoids, phenolics, saponins and tannins. The biological activities exhibited by B. speciosus and the phytochemical compounds isolated from the species include anti-arthritic, antibacterial, antigonococcal, antimycobacterial, antifungal, anti-HIV, anti-inflammatory and antioxidant activities. Future research should focus on toxicological screening, in vivo studies and clinical trials involving the crude extracts and phytochemical compounds isolated from the species.